PEMBUATAN KOMPOS, BIOCHAR DAN MOL UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KECAMATAN INGIN JAYA ACEH BESAR - muyassir muyassir; Manfarizah Manfarizah; Yadi Jufri; Cut Khairani (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2021)
Raw materials for compost making, local microorganisms (MOL), and biochar are widely available in the District of Ingin Jaya. So far, municipal waste, agricultural waste, and household waste have not been managed properly, are seen as worthless products, and cause environmental and aesthetic problems. These wastes can be converted into economically viable products such as compost, MOL and biochar. However, the community's mastery of science and technology is still very limited to converting these materials into products of economic value. Therefore, PKMBP activities were carried out through a participatory approach which was followed by field schools. The goal is to improve the capabilities and skills of the partner group consisting of members of farmer groups, PPL, PPL self-supporting in mastering the science and technology of composting, and MOL and Biochar making. The result achieved was that the PKMBP activity could increase the community's capacity in mastering the concepts, manufacturing, and application techniques of compost, MOL, and Biochar using simple technology. The community can use these products as environmentally friendly fertilizers, increase land productivity and farm efficiency. This activity can also improve the quality of waste into products of economic value, increase community turnover and overcome health problems and environmental aesthetic values.